Research in Educational Policies: thematic choices and sources in debate (2000-2010) - Antonia Almeida Silva; Márcia Aparecida Jacomini (Revista de estudios teóricos y epistemológicos en política educativa, 2019)
The study problematizes the characteristics of master's and doctoral research and their delineations regarding thematic choices and research’s sources in the field of educational policies. In order to accomplish this, we use a database of theses and dissertations presented from 2000 to 2010 in Postgraduate Programs of Education in Brazil, organized by two research projects developed between 2012 and 2017, which allows the debate between empirical findings and analyzes of influential authors in the area, identified as those most mentioned in the productions. The analysis made dialogue with the diagnostics of the scarce accumulation of knowledge, the abundance of sectorial studies and without the desired verticalization. The results point to thematic dispersion, with studies focusing on specific educational policies, especially those of recent periods. The main sources used by post-graduate students were official documents on government actions and legislation, especially on education.